Study of cardiac manifestations in hypothyroid patients admitted in tertiary care centre - Shah, Parshv P.; Parikh, Harvy; Shah, Hemant; Doctor, Nilesh (International Journal of Advances in Medicine, 2021)
Background: Hypothyroidism is the most common pathological hormone deficiency. To study various cardiac manifestations in overt and subclinical hypothyroidism. Methods: The cross-sectional analytic study is carried out on 60 patients of hypothyroid subjects in indoor facility of general medicine department in SMIMER hospital. Results: This study shows positive correlation between thyroid stimulating hormone (TSH) level, electrocardiogram (ECG) and echocardiographic findings. In this study, there is female predominance, ECG findings most commonly suggestive of sinus bradycardia and ECHO findings are most commonly suggestive of diastolic dysfunction with pericardial effusion. Conclusions: The early recognition and early initiation of treatment of hypothyroidism may helpful to lowering heart changes as hypothyroidism is reversible cause for cardiac manifestation.